2014
DOI: 10.1007/s10142-014-0385-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased accumulation of the cardio-cerebrovascular disease treatment drug tanshinone in Salvia miltiorrhiza hairy roots by the enzymes 3-hydroxy-3-methylglutaryl CoA reductase and 1-deoxy-d-xylulose 5-phosphate reductoisomerase

Abstract: Tanshinone is widely used for treatment of cardio-cerebrovascular diseases with increasing demand. Herein, key enzyme genes SmHMGR (3-hydroxy-3-methylglutaryl CoA reductase) and SmDXR (1-deoxy-D-xylulose 5-phosphate reductoisomerase) involved in the tanshinone biosynthetic pathway were introduced into Salvia miltiorrhiza (Sm) hairy roots to enhance tanshinone production. Over-expression of SmHMGR or SmDXR in hairy root lines can significantly enhance the yield of tanshinone. Transgenic hairy root lines co-expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 41 publications
1
73
0
2
Order By: Relevance
“…There are a lot of successful cases in this field. In A. belladonna and A. acutangulus , biosynthesis of scopolamine was dramatically enhanced by overexpressing the committed enzymes, H6H and TRI in A. annua , the production of artemisinin was greatly promoted by overexpressing CYP71AV1 and aldehyde 11Δ(13) reductase ; in Catharanthus roseus , overexpressing strictosidine synthase led to the increased production of ajmalicine ; in Ophiorrhiza pumila , the anti‐cancer camptothecin was significantly improved by overexpressing geraniol‐10‐hydroxylase and strictosidine synthase ; in Salvia miltiorrhiza , biosynthesis of tanshinone was enhanced by different combination of the key enzymes . These cases strongly suggest that overexpression of key enzymes is a very potent tool for genetic improvement of metabolite biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…There are a lot of successful cases in this field. In A. belladonna and A. acutangulus , biosynthesis of scopolamine was dramatically enhanced by overexpressing the committed enzymes, H6H and TRI in A. annua , the production of artemisinin was greatly promoted by overexpressing CYP71AV1 and aldehyde 11Δ(13) reductase ; in Catharanthus roseus , overexpressing strictosidine synthase led to the increased production of ajmalicine ; in Ophiorrhiza pumila , the anti‐cancer camptothecin was significantly improved by overexpressing geraniol‐10‐hydroxylase and strictosidine synthase ; in Salvia miltiorrhiza , biosynthesis of tanshinone was enhanced by different combination of the key enzymes . These cases strongly suggest that overexpression of key enzymes is a very potent tool for genetic improvement of metabolite biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Photos of hairy roots and their extracts were recorded to display the correlation between colour difference and the total tanshinone content 74, 101 . The sum of dihydrotanshinone I, cryptotanshinone, tanshinone I and tanshinone II A was calculated as total tanshinones in this research.…”
Section: Methodsmentioning
confidence: 99%
“…In an attempt to enhance betalaines production, the hairy roots were exposed to metal ions [14]. It was reported that Ca 2+ , Ag + and Cd 2+ could improve the production of tropane alkaloids, scopolamine and hyoscyamine, in hairy roots cultures of Brugmansia candida [15,16] [17][18][19][20]. Among them, Ag + was considered as an effective elicitor for phenolic compound and tanshinone production in S. miltiorrhiza hairy roots and could improve rosmarinic acid, salvianolic acid B and tanshinones production.…”
Section: Effect On the Production Of Secondary Metabolitesmentioning
confidence: 99%